Student Teachers' Experiences of Constructivism in a Theoretical Course Built on Inquiry-based Learning - Sıtkıye Kuter; Bekir Özer (Anı Publishing, 2020)
This study aimed to examine what student teachers at a teacher education program, in a theoretical course built on inquiry-based learning, learned as a result of inquiring the extent of implementation of constructivist theory in instructional processes in secondary schools. The participants involved all student teachers (28) taking 'Teaching-Learning Theories and Approaches' course. Qualitative data were gathered via interviews and reflective reports, while quantitative data were collected by evaluating student teachers' reports using project evaluation rubric. The trustworthiness of the findings was ensured via triangulation, peer debriefing, and multiple coding. The findings showed that, as a result of student teachers' engagement in inquiry, they gained theoretical awareness and understanding of the instructional processes through linking theory and practice of constructivism, became aware of the factors limiting the implementation of constructivist theory, and developed their knowledge and skills related to conducting inquiry.